How Fast Fashion Lowers Production Cost but Increases Environmental Cost - Zahira, Malika; Alfakihuddin, Muhammad Lukman; Anwari, Jenifer Alexandra; Hadi, Jessica Madelyn; Kuntadi, Shiny Chutzpah; Lim, Jocelyn; Kholik, Fajar Nur (APPS Publications, 2023)
ABSTRACT - In an effort to meet the increasing demand for inexpensive, disposable goods, the fashionindustry has adopted a business model which prioritises cost effectiveness above all else. Thisbusiness model, known as ‘fast fashion’, had been reportedly known to encourage consumersto discard clothing at an alarming rate which in turn burdens landfills, creating a cycle ofwaste. This throwaway culture stemming from fast fashion raises alarms of the impact of theincessant reliance of synthetic fibres and chemically intensive processes which exacerbatesenvironmental degradation over a long period of time. Objective – This paper aims to highlight and explore the need for a shift in the fashion industry’s standards. This paper also aims to further encourage sustainable business models, advocate for consumer awareness, emphasising these factors as crucial drivers of change. Methodology – The literature review method was employed to analyze the data in order to acquire a more comprehensive understanding of the complex interrelationships among fast fashion, manufacturing costs, and environmental impacts. Findings – This paper has revealed the realistic hard and soft, short, medium and long-term solutions to attack the problem at its root cause. Furthermore, fast fashion’s impact on the environment isdetrimental and requires a dire need of reevaluation of its practices to urgently ensure a moresustainable and responsible future of the fashion industry. Novelty – For companies which indulge in the fast fashion business model like SHEIN to implement sustainable alternatives such as using eco-friendly materials and textiles, ethical labour practices, and innovative recycling methods to be used as potential solutions in order to mitigate the environmental damage caused by the fast fashion industry and possibly encourage their consumers to understand thedamage caused by the cycle of waste.